Pengaruh Kebijakan Pemerintah melalui Media Massa terhadap Keputusan Melakukan Vaksinasi Covid-19 di Kalangan Mahasiswa - Detty Widyaningsih; Rizca Haqqu (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this study was to determine the effect of government policies through the mass media on students' decisions in West Java to vaccinate against Covid-19. The method used by researchers is simple linear regression analysis. The sample used in this study was 100 students in West Java. The results of this study indicate that there is a significant influence between government policies in the mass media on students' decisions to vaccinate Covid-19. The R Square results found that the effect of government policy on the mass media on the decision to vaccinate Covid-19 was 49.8%. While the remaining 50.2% is explained by other variables not included in this research model. The conclusion of this study is that government policies in the mass media have a significant effect on students' decisions to vaccinate Covid-19. Keywords: Covid-19, Government policy, Vaccinate